Pomegranate 3 (February 1998) - (:unkn) unknown (The Pomegranate, 1998)
The Myth of Historical Narrative: Margaret Murray's The God of the Witches / by Nancy Ramsey -- Excavating Sites of Production: Margaret Murray's Theory of Religion in Context / by Pam A. Detrixhe -- James George Frazier's The Golden Bough: A Critical Approach / by Fritz Muntean -- Book Review: The Witch in History: Early Modern and Twentieth-Century Representations / review by Ronald Hutton -- The Pomegranate: Reader's Forum
The Pomegranate: A New Journal of Neopagan Thought
1 Electronic record(s) and derivatives. PDF file. 28 pages.
Keywords: Periodicals; Murray, Margaret Alice. God of the witches; Murray, Margaret Alice--Criticism and interpretation; Murray, Margaret Alice--Influence; Frazer, James George, 1854-1941. Golden bough; Frazer, James George, 1854-1941--Criticism and interpretation; Purkiss, Diane, 1961- Witch in history--Reviews; Wicca--Influence; Book reviews; Literary criticism